Elevation of arginine vasopressin levels following loop diuretic therapy as a prognostic indicator in heart failure. (December 2016) - Kitada, Shuichi; Kikuchi, Shohei; Sonoda, Hiroo; Yoshida, Atsuhiro; Ohte, Nobuyuki
Objective: To investigate the association between arginine vasopressin (AVP) levels and loop diuretic (LD) therapy in patients with heart failure and to determine if AVP levels are a prognostic indicator of treatment failure. Methods: Patients with stable heart failure and reduced (< 40%) left ventricular ejection fraction (LVEF) were divided into those treated with (LD) or without LD (NLD). The LD group was separated into subgroups of high (> 6.5 pg/dl) and low (≤ 6.5 pg/dl) AVP levels. The clinical and biochemical characteristics of the two groups were compared and the prognostic value of AVP levels in heart failure evaluated. Results: Of the 63 patients enrolled into the study, 41 (65.1%) were in the LD group and 22 (34.9%) were in the NLD group. Despite no differences between groups in LVEF, creatinine clearance, or brain natriuretic peptide, the LD group had significantly higher AVP levels compared with the NLD group. A Cox proportional-hazards model showed that AVP was an independent predictor of adverse events. In addition, the elevation in AVP in the LD group was inversely correlated with an increase in free water clearance but not serum osmolality and was related to poor outcome. Conclusions: Elevated AVP levels in patients with heart failure who received LD therapy were associated with a poor prognosis. Loop diuretics may induce non-osmolar AVP release, which can worsen heart failure.